Proceso de atención de enfermería en paciente escolar con apendicectomía. - Arias González, Freddy Rogelio (2022)
The present work gives rise to the creation of a clinical case with a selected theme of a school patient with appendicitis. This case is often represented at the Noboa Montenegro Hospital in the city of Guaranda, in the Pediatrics area. For this clinical case, a methodology was used where the patient's clinical history, general habits, staff monitoring for improvement and incorporation into their daily lives are known. Likewise, a theoretical framework is deepened where information is sought about appendicitis that different authors tell us. Appendicitis is and will continue to be a common pathology in pediatric patients and one of the main causes of hospital admission in a health unit. Appendicitis in a pediatric patient is accompanied by symptoms such as nausea, vomiting, hyperthermia of 38°C, cramping abdominal pain in the right iliac fossa that requires immediate surgical intervention (appendectomy) for the slight recovery of the patient.